Pemanfaatan Limbah Ikan Nila sebagai Pupuk Organik Pakcoy secara Hidroponik di Desa Dolok Sagala, Serdang Bedagai - Gunawan, Hari; Febrianto, Eka Bobby; Mahyunis, Mahyunis; Lumbanraja, Rafhael Albertus; Simarmata, Alex Paul Hendry; Simanullang, Putra Sakti; Manullang, Raymond; Wahyuni, Seri; Hidayah, Nur (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
This Community Service Program was conducted to introduce and implement hydroponic technology that utilizes waste from Nile tilapia farming as a source of organic fertilizer. This activity was located in Dolok Sagala Village, Dolok Masihul District, Serdang Bedagai Regency. The method used in this PKM included training and direct mentoring of the community in creating and managing a hydroponic system for cultivating Brassica Rapa plants. This activity showed that the hydroponic system using fish waste as organic fertilizer produced high-quality Brassica Rapa plants. Additionally, this program provided the community with new knowledge about the benefits and potential of hydroponic technology as a modern agricultural solution in limited land areas. The success of this program is expected to be adopted more widely by the community to enhance local food security and economic welfare.